1984
DOI: 10.3382/ps.0632027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyclic and Constant Ambient Temperatures on Feed Consumption, Egg Production, Egg Weight, and Shell Thickness of Hens

Abstract: Groups of 18 hens, 230 days of age, were housed in each of three climatic chambers with light schedules of 14L:10D. One was maintained at a constant temperature of 23.9 C, the second was cycled between 15.6 and 37.7 C (mean, 26.7 C), and the third was cycled between 21.1 and 37.7 C (mean, 29.4 C). In Experiment 1, the high temperature peaked during the dark period at 0200 hr and in Experiment 2, the high temperature peak was at 1400 hr during the light period. The birds had free access to a commercial breeder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 13 publications
(18 reference statements)
3
25
0
2
Order By: Relevance
“…The minimum requirement for the maximal eggshell quality was found to be 50-100 mg/kg. Our overall results show that sup- Eggshell breakage is known to be directly related to the quality of the shell, which can be affected by nutrition and breeding conditions (Emery et al, 1984;Tůmová et al, 2009). It is well established that trace elements may affect eggshell quality by their catalytic properties as key enzymes involved in the process of membrane and eggshell formation, or by interaction directly with the calcite crystals in the formation of eggshells (Zamani et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
“…The minimum requirement for the maximal eggshell quality was found to be 50-100 mg/kg. Our overall results show that sup- Eggshell breakage is known to be directly related to the quality of the shell, which can be affected by nutrition and breeding conditions (Emery et al, 1984;Tůmová et al, 2009). It is well established that trace elements may affect eggshell quality by their catalytic properties as key enzymes involved in the process of membrane and eggshell formation, or by interaction directly with the calcite crystals in the formation of eggshells (Zamani et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
“…Decreases in BW gain were recorded in broilers exposed to temperatures of 31 to 36°C and 28 to 36ºC (QuinteiroFilho et al, 2010). Furthermore, Emery et al (1984) showed that laying hens under cycling temperatures, ranging between 21.1 to 37.7°C, lost more BW than birds at a constant temperature of 23.9°C, which was largely attributed to reduced feed consumption.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Gao et al (1999) reported that, when external house temperature was high, broiler feed intake, feed conversion ratio, and growth rate were reduced. In heat-stressed layers, reduced food intake led to a decrease in egg production and reduced egg weight and quality (Emery et al, 1984).…”
Section: Effects Of Heat Stress On the Daily Behavior Of Wenchang Chimentioning
confidence: 99%